The Curriculum Implementation for Cross-Cultural and Global Citizenship Education in Indonesia Schools - Wahyudin, Dinn; Suwirta, Andi (EDUCARE, 2017)
ABSTRACT: The CCE (Cross-Cultural Education) and GCE (Global Citizenship Education) are two issues now newly attracting attention with the focus on universal human rights and global issues. If the first is a process of education by which individuals and groups can learn to internalize the facts of cultural pluralism to bring about a society that recognizes cultural diversity; while the later is about educating the qualifications, qualities, rights, and responsibilities of global citizens. Many efforts have been made by MoEC (Ministry of Education and Culture) of the Republic of Indonesia to reform the education system and redesign system of curriculum. One of hot issue is concerning with cross culture and global citizenship that can be implemented in primary school as well as secondary school curriculum, as it is one of the requirements in implementing the SDGs (Sustainable Development Goals). The paper, by using the qualitative method and explanation descriptively, discussed some topics concerning CCE and GCE. They are: (1) informing policies and programs lead by MoEC of the Republic of Indonesia in redesigning of new curriculum that give more spaces for increasing the CCE and GCE; (2) identifying general trends as well as indigenous aspects in supporting and enriching teaching-learning activities related to cross-cultural and global education for heterogeneous students; (3) presenting best practices created by schools in developing school culture and global citizenship that empowering students from diverse races, religions, ethnics, and cultural groups; and (4) identifyingÂ  schools efforts in developing cross-cultural and global citizenship curriculum as meaningful learning experience for students.KEY WORDS: Cross-Cultural Education; Global Citizenship Education; Curriculum Development; Education Sustainable Development; Indonesia Schools.Â Â About the Authors: Prof. Dr. Dinn Wahyudin is a Lecturer at the Faculty of Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. Andi Suwirta, M.Hum. is a Lecturer at the Faculty of Social Studies Education UPI in Bandung, West Java, Indonesia. For academic interests, the authors can be contacted via their e-mails at: dinn_wahyudin@upi.edu and suciandi@upi.eduSuggested Citation: Wahyudin, Dinn & Andi Suwirta. (2017). âThe Curriculum Implementation for Cross-Cultural and Global Citizenship Education in Indonesia Schoolsâ in EDUCARE: International Journal for Educational Studies, Volume 10(1), August, pp.11-22. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877. Article Timeline: Accepted (March 2, 2017); Revised (June 1, 2017); and Published (August 30, 2017).